From pre- and in-service teachers’ asymmetric backgrounds to equal co-teaching: Investigation of a professional learning model - Kervinen, Anttoni; Portaankorva-Koivisto, Päivi; Kesler, Merike; Kaasinen, Arja; Juuti, Kalle; Uitto, Anna (Frontiers in Education, 2022)
The existing co-teaching practices in teachers’ professional learning emphasize collaboration between pre-service and in-service teachers. Although this collaboration is usually defined by a mentor–student relationship with asymmetric power relations, successful co-teaching practices in schools are considered to involve parity, resulting in mutual learning for all involved parties. In this study, we designed a model for teachers’ professional learning in which pre- and in-service teachers collaborate and have shared goals, with the aim of equal responsibilities for planning and implementing instruction, despite the teachers’ diverse backgrounds. During the four years of piloting and developing the model in the Finnish teacher education context, we investigated how the participants reflected on the co-teaching process. We analyzed data from collaborative reflection sessions to identify the challenges and benefits of this untypical form of collaboration. The findings showed that asymmetric backgrounds may cause challenges, but that if these are overcome, they can also create opportunities for valuable co-teaching experiences for all the participants. Helping the participants initiate the co-teaching process and take different roles appeared to be essential for a successful process. We discuss the findings regarding the development of co-teaching practices in teacher education and in schools.